The practice of assessment for learning in the teaching of English language writing Madrasah Aliyah Negeri (MAN) 1 Medan - Asro, Kholijah (Kulliyyah of Education, Internatinonal Islamic University Malaysia, 2016)
The objective of this study is to examine the practice of assessment for learning in the teaching of English writing of secondary school students in Madrasah Aliyah Negeri (MAN) 1 Medan. It further attempts to identify the factors underlying students' view of assessment for learning (AfL) in English writing class. It also identifies the factors that are most and least influencing on students' view of AfL and the consistent factors in understanding this assessment. The present study formulated the self-constructed questionnaire for the assessment for learning based on the framework proposed by Black and Wiliam (2006).The questionnaire was distributed to 386 students. A 5-Likert-type scale was used to measure the factors influencing Assessment for Learning in English writing. Factor analysis using the Principal Component Analysis (PCA) was applied to examine the practice of assessment for learning in the teaching of English writing. The finding of this study shows there are five factors underlying students' view of Assessment for Learning (AfL) in English writing which are formative feedback, sharing learning intention, students' involvement in assessment, students' learning reference and metacognition in learning. Recommendations for future studies on assessment for learning with other frameworks on students were also given.